Chenopodium khorasanica (Amaranthaceae), a new species from Iran - Hamdi, Seyed Mohammad Mahdi; Assadi, M.; Malekloo, M.; Jouharchi, M. R. (Acta Biologica Szegediensis, 2016)
Chenopodium khorasanica (Amaranthaceae) is described as new species from north-east of Khorasan province (Iran). The new species is compared with its closest relative Chenopodium sosnowskyi Kappeler and Chenopodium vulvaria L.. This species is similar to Ch. sosnowskyi in having hair shape of leaf, habit and petiole size. Ch.khorasanica differs from Ch. sosnowskyi in having stem height, hair length of leaf, hairs density surface of leaf, inflorescence height, number of flowers in gap, ornamentation of surface cell of seed. This species similar to Ch. vulvaria in having hair shape of leaves, petiole length and without stomata of perianth surface leaf margin and number of flowers in gap. This species differs from Ch. vulvaria in having stem height, habit, blade shape of leaf, hairs length of leaf, hair density surface of leaf, smelling of decaying fish and leaf dorsal color. Information about the species, morphology, micromorphology, habitats and distribution is provided.